CNS Aspergillosis (Anwer Khan Modern Medical College Journal, 2022)
Cerebral aspergillosis has the tendency to occur in immune-compromised patients. Less commonly, immune-competent individuals can be affected, with neuroimaging findings being difficult to interpret. A surgical excision with aggressive antifungal therapy is required for a proper management. This case report describes an immune-competent patient with cerebral aspergillosis that presented radiologically as a suspicious mass to be diagnosed pathologically and excised surgically.AKMMC J 2021; 12(2): 107-112